2017
DOI: 10.1016/j.ufug.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of urban habitats in the abundance of red squirrels (Sciurus vulgaris, L.) in Finland

Abstract: Because the amount of urban areas has increased, it is important to investigate the abundance of wildlife species in relation to urban environments. Analyzing the impact of urbanization on the presence of forest-dwelling mammals is of interest due to the possible effects of urbanization on human-wildlife relationships and urban biodiversity. The Eurasian red squirrel (Sciurus vulgaris) is a declining forest species, and its occurrence in urban environments has been inadequately studied. The loss and fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…Ims (1990) reported a positive correlation between dispersal distance and avoidance behaviour in female grey-sided voles, Myodes rufocanus and during peaks of population densities meadow vole Microtus pennsylvanicus males that dispersed were more aggressive than others (Myers and Krebs 1971). Human induced changes, such as climate change (Bradshaw and Holzapfel 2006), the spread of urbanization (Parker and Nilon 2012;Jokima¨ki et al 2017) and habitat fragmentation (Verboom and Van Apeldoorn 1990), has forced individuals to either adapt to these changes or disperse, and such changes may be more detrimental to individuals displaying certain traits. Therefore, depending on temperament, individuals within a population may vary in their potential to occupy areas with different levels of disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ims (1990) reported a positive correlation between dispersal distance and avoidance behaviour in female grey-sided voles, Myodes rufocanus and during peaks of population densities meadow vole Microtus pennsylvanicus males that dispersed were more aggressive than others (Myers and Krebs 1971). Human induced changes, such as climate change (Bradshaw and Holzapfel 2006), the spread of urbanization (Parker and Nilon 2012;Jokima¨ki et al 2017) and habitat fragmentation (Verboom and Van Apeldoorn 1990), has forced individuals to either adapt to these changes or disperse, and such changes may be more detrimental to individuals displaying certain traits. Therefore, depending on temperament, individuals within a population may vary in their potential to occupy areas with different levels of disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…While Parker and Nilon's (2008) observed grey squirrels at higher densities to be more aggressive, the opposite was found in the current study. Unaggressive, shy (reactive) individuals have been shown to display more flexible behaviour (Koolhaas et al 1999), and may therefore demonstrate a greater tolerance to conspecifics. Sih et al (2004) observed how proactive individuals are both aggressive and bold and while they tend to dominate and out-compete reactive ones in a stable environment, reactive individuals appear to respond better to changing environments (Sih et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…That buildings were actually preferred is supported by our previous analysis, where the habitat use of squirrels in an urban area was studied (Hämäläinen et al, ). It is possible that squirrels moved through built areas in order to utilize supplement feeding provided by humans (Jokimäki et al, ). In the rural area, the observed preference for young forests was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a potential reason for the observed differences between urban and rural area is related to differences in settlement decisions. Resource availability and density of individuals determine settlement decisions of dispersing squirrels (Merrick & Koprowski, 2017a;Selonen & Hanski, 2012) and are known to be potentially higher in the urban area than in rural areas for red squirrels (Haigh, Butler, O'Riordan, & Palme, 2017;Jokimäki, Selonen, Lehikoinen, & Kaisanlahti-Jokimäki, 2017). In the urban area, food availability is more stable than in rural areas, as there are multiple tree species and additional feeding provided by humans.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the field of remote sensing is rapidly advancing (Kwok 2018), with increasing numbers of sensors, targeted missions for ecology (Wikelski et al 2007, Bioucas-Dias et al 2013, Jetz et al 2016, freely available data, and improved access to data analysis pipelines (Gorelick et al 2017, Murray et al 2018). These biodiversity data, combined with remotely sensed data, are increasing our understanding of biodiversity responses to environmental change (Pettorelli et al 2014a(Pettorelli et al , b, 2016, especially at macro-ecological scales (Hochachka and Fink 2012, La Sorte et al 2014, Jokimäki et al 2017, Horton et al 2018, including bird responses to urbanization (Bino et al 2008). But in regards to urbanization, how well do macro-ecological responses correspond with local-scale responses?…”
Section: Introductionmentioning
confidence: 99%